Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12885-017-3907-z
|View full text |Cite
|
Sign up to set email alerts
|

Gene-expression signature regulated by the KEAP1-NRF2-CUL3 axis is associated with a poor prognosis in head and neck squamous cell cancer

Abstract: BackgroundNRF2 is the key regulator of oxidative stress in normal cells and aberrant expression of the NRF2 pathway due to genetic alterations in the KEAP1 (Kelch-like ECH-associated protein 1)-NRF2 (nuclear factor erythroid 2 like 2)-CUL3 (cullin 3) axis leads to tumorigenesis and drug resistance in many cancers including head and neck squamous cell cancer (HNSCC). The main goal of this study was to identify specific genes regulated by the KEAP1-NRF2-CUL3 axis in HNSCC patients, to assess the prognostic value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 56 publications
(64 reference statements)
4
52
0
Order By: Relevance
“…The underlying mechanism is not yet clear. Nevertheless, the TCGA data showed that overexpression of the GSR, GCLC, and TXNRD1 were highly enriched in KEAP1-mutant lung adenocarcinoma (P ¼ 1.2 Â 10 À8 , 1.0 Â 10 À6 , and 1.4 Â 10 À9 , respectively) and in NFE2L2-mutant lung squamous cell cancer (P ¼ 1.5 Â 10 À3 , 4.7 Â 10 À4 , and 6.1 Â 10 À9 , respectively), supporting the roles of the KEAP1/NRF2 pathway in regulation of the expression of these oxidative stress-associated genes (37). It is possible that, unlike mutations in KEAP1/NRF2 pathways, low expression of GSR alone is not sufficient to trigger TXNRD1 overexpression.…”
Section: Discussionmentioning
confidence: 63%
“…The underlying mechanism is not yet clear. Nevertheless, the TCGA data showed that overexpression of the GSR, GCLC, and TXNRD1 were highly enriched in KEAP1-mutant lung adenocarcinoma (P ¼ 1.2 Â 10 À8 , 1.0 Â 10 À6 , and 1.4 Â 10 À9 , respectively) and in NFE2L2-mutant lung squamous cell cancer (P ¼ 1.5 Â 10 À3 , 4.7 Â 10 À4 , and 6.1 Â 10 À9 , respectively), supporting the roles of the KEAP1/NRF2 pathway in regulation of the expression of these oxidative stress-associated genes (37). It is possible that, unlike mutations in KEAP1/NRF2 pathways, low expression of GSR alone is not sufficient to trigger TXNRD1 overexpression.…”
Section: Discussionmentioning
confidence: 63%
“…However, we now have evidence that constitutive NRF2 activation via mutations in KEAP1 or recurrent NFE2L2 exon 2 deletions can drive tumor proliferation and metastasis [70,67]. NFE2L2 mutations have recently been shown to define subtypes with differential prognosis in lung and head and neck cancers [71,72,73,74]. Several upcoming clinical are designed to explore the therapeutic benefit of compounds that inhibit NRF2 in advanced cancer patients harboring mutations in NFE2L2 or KEAP1 [75,76,77].…”
Section: Crso Prioritized Nfe2l2 Combinations In Multiple Cancersmentioning
confidence: 99%
“…Our approach of semi-quantitative normalization of tumor staining intensity by comparing it with adjacent epithelium might be furthermore supported by a study from Namani et al, where RNAseq data from the TCGA HNSCC cohort were normalized against normal tissue expression and subsequently lead to a signature of overexpressed oxidative stress response genes including AKR1C1 and AKR1C3. 33 For confirmation, we analyzed 25 The AKR1Cs 1 and 3 are known to catalyze the production of retinol isoforms from retinaldehyde and subsequently lowering retinoic acid concentrations. 37 Retinoic acid is a known inhibitor of NRF2 function, therefore decreased concentrations of retinoic acid lead to additional NRF2 activation.…”
Section: Discussionmentioning
confidence: 99%